Econometric Evaluation of Asset Pricing Models - Hansen, Lars Peter; Heaton, John; Luttmer, Erzo G. J. (Review of Financial Studies, 1995)
In this article we provide econometric tools for the evaluation of intertemporal asset pricing models using specification-error and volatility bounds. We formulate analog estimators of these bounds, give conditions for consistency, and derive the limiting distribution of these estimators. The analysis incorporates market frictions such as short-sale constraints and proportional transactions costs. Among several applications we show how to use the methods to assess specific asset pricing models and to provide non-parametric characterizations of asset pricing anomalies.